Three new species of terrestrial frogs Pristimantis (Anura: Craugastoridae) from the upper basin of the Pastaza River, Ecuador - Reyes-Puig, Juan Pablo; Reyes-Puig, Carolina Pilar; Ramírez-Jaramillo, Salomón R.; Pérez-Lara, María B.; Yánez-Muñoz, Mario H. (ACI Avances en Ciencias e Ingenierías, 2014)
We describe three new species of terrestrial frogs Pristimantis from the evergreen montane forests surrounding the Tungurahua Volcano in the Upper Pastaza River Basin, eastern foothills of Ecuador.The first species is distinguished by the distinctive shape of its digits (elongated, narrow and only slightly wider than finger discs); the second presents cranial crest and body size smaller than 31 mm; and the third is spiny and exhibits a distinctive pattern with red-wine finely delineated by cream.
Keywords: evergreen montane forests; Pristimantis marcoreyesi sp. nov.; Pristimantis punzan sp. nov.; Pristimantispuruscafeum sp. nov.; Terrarana; Tungurahua Volcano